Lysophospholipids Facilitate COPII Vesicle Formation - Melero, Alejandro; Chiaruttini, Nicolas; Karashima, Takefumi; Riezman, Isabelle; Funato, Kouichi; Barlowe, Charles; Riezman, Howard; Roux, Aurélien (Current biology, 2018)
Coat protein complex II (COPII) proteins form vesicles from the endoplasmic reticulum to export cargo molecules to the Golgi apparatus. Among the many proteins involved in this process, Sec12 is a key regulator, functioning as the guanosine diphosphate (GDP) exchange factor for Sar1p, the small guanosine triphosphatase (GTPase) that initiates COPII assembly. Here we show that overexpression of phospholipase B3 in the thermosensitive sec12-4 mutant partially restores growth and protein transport at non-permissive temperatures. Lipidomics analyses of these cells show a higher content of lysophosphatidylinositol (lysoPI), consistent with the lipid specificity of PLB3. Furthermore, we show that lysoPI is specifically enriched in COPII vesicles isolated from in vitro budding assays. As these results suggested that lysophospholipids could facilitate budding under conditions of defective COPII coat dynamics, we reconstituted COPII binding onto giant liposomes with purified proteins and showed that lysoPI decreases membrane rigidity and enhances COPII recruitment to liposomes. Our results support a mechanical facilitation of COPII budding by lysophospholipids. [Display omitted] •COPII mutant sec12-4 is rescued by the overexpression of an ER resident phospholipase•Lipidomic analysis of COPII vesicles shows enrichment in lysophospholipids•Recruitment of COPII proteins to liposomes increases in presence of lysophospholipids•Lysophosphatidylinositol lowers the rigidity of membranes in vitro Melero et al. show that lysophospholipids are enriched in COPII vesicles and facilitate their formation. These highly conical lipids can lower the energy required to deform membranes and increase the recruitment of COPII coats to giant liposomes in vitro. Their results show that lysophosphatidylinositol strongly facilitates COPII vesicle formation.